Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1136/bjophthalmol-2017-311429
|View full text |Cite
|
Sign up to set email alerts
|

The impact of SIGN glaucoma guidelines on false-positive referrals from community optometrists in Central Scotland

Abstract: Patients referred after the introduction of SIGN guidelines were 33.5% less likely to be discharged at the first visit. Although compliance to most recommendations in SIGN guidelines has improved, there is still a need to improve adherence to referral criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 18 publications
(18 reference statements)
0
19
0
Order By: Relevance
“…Since then, SIGN 144 (Glaucoma referral and safe discharge) 34 has been published and this too appears to have afforded a further improvement in referral accuracy. In a retrospective study, Sii et al 35 observed a significant decline in the first visit discharge rate when comparing two 2-month periods both before (29.2% first visit discharge rate) and after (19.2% first visit discharge rate ) the publication of SIGN 144, while also observing room for improved adherence to referral criteria. On a more specific clinical query, Annoh et al 36 recently examined the accuracy of referrals for primary angle closure related diagnoses in Scotland.…”
Section: Effectiveness Of Traditional Case Finding and Grfsmentioning
confidence: 99%
“…Since then, SIGN 144 (Glaucoma referral and safe discharge) 34 has been published and this too appears to have afforded a further improvement in referral accuracy. In a retrospective study, Sii et al 35 observed a significant decline in the first visit discharge rate when comparing two 2-month periods both before (29.2% first visit discharge rate) and after (19.2% first visit discharge rate ) the publication of SIGN 144, while also observing room for improved adherence to referral criteria. On a more specific clinical query, Annoh et al 36 recently examined the accuracy of referrals for primary angle closure related diagnoses in Scotland.…”
Section: Effectiveness Of Traditional Case Finding and Grfsmentioning
confidence: 99%
“…In Scotland, the Scottish Intercollegiate Guidelines Network (SIGN) is the body designed to develop evidencebased clinical guidelines for the National Health Service. 15 In 2015, SIGN published updated national clinical guidelines on glaucoma referral and safe discharge, which state that optic disc appearance should be categorised according to the DDLS system and that optometrists should consider 15 Several studies have examined the quality of glaucoma referrals by optometrists in Scotland 12,14,19,20 ; however to our knowledge this study is the first attempt to specifically examine the role of the DDLS. The study has several interesting findings.…”
Section: Discussionmentioning
confidence: 99%
“…As DDLS can be determined without recourse to expensive imaging equipment, it provides a cheap method of assessing glaucomatous structural damage that could potentially be used by optometrists, and particularly those who lack access to OCT, to improve the accuracy of decisions regarding whether patients should be referred or treated for possible glaucoma. Improving accuracy of referrals to ophthalmology services is important given that studies in the United Kingdom have shown first visit discharge rates (FVDRs) among patients referred to ophthalmologists due to suspected glaucoma of 19.4% to 43%, implying a high number of false positive referrals 12,13,14 . The 2015 Scottish Intercollegiate Guidelines Network (SIGN) glaucoma guidelines 15,16 included the recommendation that optometrists assess DDLS and provide this information when referring patients with suspected glaucoma.…”
Section: Introductionmentioning
confidence: 99%
“…A number of peer‐reviewed studies have evaluated aspects of the new Scottish GOS contract including the quality of referrals, access to and distribution of services, the use of clinical equipment and practitioner preferences relating to the management of ocular conditions. One particular area that has attracted the attention of researchers is the impact of the new GOS contract on the quality of glaucoma referrals . Comparing the quality of more than 300 glaucoma referrals before and after the new GOS, Ang et al .…”
Section: Comparison Between Eye‐care Models and Supporting Evidencementioning
confidence: 99%
“…In a recent paper the impact of the SIGN glaucoma guidelines on community optometrists’ glaucoma referrals was assessed. The study found that there is still room for improved adherence to referral criteria and it was pointed out that reasons for lower than anticipated adherence may include the complexity of some of the guidance tools …”
Section: Comparison Between Eye‐care Models and Supporting Evidencementioning
confidence: 99%